Defect‐Passivation Using Organic Dyes for Enhanced Efficiency and Stability of Perovskite Solar Cells. Issue 5 (6th May 2020) - Xiong, Shaobing; Song, Jingnan; Yang, Jianming; Xu, Jinqiu; Zhang, Ming; Ma, Ruru; Li, Danqin; Liu, Xianjie; Liu, Feng; Duan, Chungang; Fahlman, Mats; Bao, Qinye
Abstract : Defect Passivation In article number 1900529, Qinye Bao and co‐workers propose a strategy using abundant and color organic dyes as an additive to passivate defect states and to produce more n‐type perovskite films, which remarkably increases the power conversion efficiency of perovskite solar cells. The rich hydrogen bonds and carbonyl structures in the organic dye can significantly enhance the device stability both in terms of humidity and thermal stress.